Implementation of the Project Management Office (PMO) in companies in the financial sector (Revista de Investigaciones Universidad del Quindío, 2023)
The financial sector is the backbone of the world economy, over the years this has been faced with many crises that have been catastrophic for all countries and global economic sectors in terms of loss of capital and resources, which have forced to implement changes in their economic and financial models; this is how today there are global changes and conflicts that live in different nations that are world powers, or even in our country with the various political changes and legislation, which greatly affects the economy. It is for this reason that the financial sector is faced with the need to make structural changes or changes to its services, which are high impact projects for its clients.Over the years, project management has become much stronger due to its positive impact on all economic sectors, which has given added value to organisations and an efficient development of their projects in terms of scope, cost and time, which is why the Project Management Office (PMO) has emerged as a central unit in which the projects that are executed can be solved in terms of knowledge, lessons learned through the basis, methodologies and tools for the proper implementation of projects; For this reason, the financial sector is no stranger to the implementation of a PMO within its organisational structure.This article presents a group of theoretical and technical concepts of everything related to the PMO, which are addressed from the individual to the collective in order to highlight the main fundamentals to be taken into account in the implementation of a PMO in order to make a value proposition for its customers. The aim of this article is to analyse the academic foundations of a project manager, in order to develop the capabilities and skills in project management in order to have a criterion focused on the implementation of the Project Management Office - PMO that benefits the processes of an organisation with a view to continuous improvement and delivery of good customer service.
Keywords: Financial sector; management; projects; areas of expertise; cost-benefit